Experimental investigation on exterior RC beam-column connections subjected to cyclic loading using steel and shape memory alloy (SMA) reinforcing bars - Hossein Rezaee Azariani (Iranian Society of Structrual Engineering (ISSE), 2019)
In the present Experimental research, the behavior of exterior RC beam-column connections subjected to cyclic loading is studied using steel and shape memory alloy (SMA) reinforcing bars. In this research, 8 specimens of exterior RC beam-column connections were tested in which four specimens included SMA reinforcing bars and the remaining four specimens included steel bars. The confinement of beam longitudinal bars was different in the connections. Also, two types of concretes were used with the strengths 30 and 45 MPa, respectively.The specimens were tested under cyclic loading. The results of the research show that the specimens with SMA reinforcing bars can return to their initial shape after tolerating large displacements. In these specimens, the energy dissipation is satisfactory and the decrease in the residual deformation is significant. According to the superelastic behavior of the SMA reinforcing bars, the width of cracks is not significant in the connection core and cyclic loading reduced the cracks in the connection core. As the cyclic loading increased, bending failure occurred in the beam outside of the connection core. As the concrete strength and confinement value increased, bending failure still occurred in the beam outside of the connection core. In the beam-column connection with steel bars, shear failure occurred in the connection core. However, as the concrete strength and confinement increased, bending failure occurred in the beam outside of the connection core. Plastic hinge length in the connecting beams were calculated in the specimens with SMA and steel bars by empirical equations and compared with the test results. It was shown that Paulay and Priestley equations were suitable to be used for concrete connections with different bars.